Aristotle’s Virtue Ethics and Akinpelu’s Moral Philosophy as Paradigms of Education for Moral Integrity in Nigeria (2013)
Moral corruption seems to be a bane of Nigeria’s development. Lack of moral integrity manifests in fraud, dishonesty and subversion of truth, justice and due process in all facets of national life. This necessitates a comprehensive moral education programme to develop moral integrity in the coming generations of Nigerians. Previous studies have focused on indoctrinative approach to moral education. This has failed to adequately account for the role of reasoning in moral action and decision making. This study, therefore, examined the concept of moral integrity in the context of reason based moral philosophies of Aristotle and Akinpelu by clarifying their relationship with reference to the moral problems that are prevalent in Nigerian society. This is in an attempt to develop an educational programme that fosters production of morally autonomous individuals. The study adopted analytic, speculative and prescriptive methods of philosophical investigation. Conceptual analysis was used to clarify the concept of moral integrity in the ideas expressed in Aristotle’s Nicomachean Ethics and Akinpelu’s Essays in Philosophy and Education and other relevant publications and documents. The prescriptive method guided the examination of what makes moral integrity a worthwhile human quality and how it can be cultivated through education. Speculation guided in discussing whether moral integrity as an ideal is attainable or not and the role which education can play in its attainment. Moral integrity is a cluster concept which ties together other overlapping concepts such as honesty, sincerity, constancy, consistency and sound judgement to discern moral issues and act consistently on principles that can promote social harmony. It is also constitutive of some virtues such as courage, temperance, continence, practical wisdom and other- regarding virtues such as honesty, fairness, justice and sensitivity. The two philosophers subscribe to a rational approach to moral education. However, while Aristotle places more emphasis on moral habituation which means inculcation of appropriate character traits through constant practices, Akinpelu emphasises development of learner’s capacity for moral reasoning. These two approaches informed the proposed Integrative Moral Education Model which draws from the strengths of the ideas of the two philosophers. The model advanced that moral education be integrated into the entire aspect and culture of school life. With respect to programmes of learning, drawing out the moral dimensions of academic subjects would enhance learners’ capacity for moral reasoning when the focus is on the social values that are inherent in the content and methods of teaching and learning academic subjects. Programmes of activities and programmes of guidance would contribute to deliberate exposure of learners to actions that can make them to experience and cognitively internalise worthwhile habits required to develop learners’ moral knowledge, sensitivity and sense of judgement. The ideas of the two philosophers are complementary as philosophical frameworks for a moral education programme to cultivate moral integrity in Nigeria. Other social institutions such as the home, the government, and the media should be strengthened to complement the efforts of educational institutions to educate coming generations of Nigerians for moral integrity.